Differences in the tooth impaction characteristics between males and females nonsyndromic cleft lip and palate patients: a cross-sectional study - Andreas, Monica; Laviana, Avi; Mardiati, Endah; Sayuti, Elih; Noviaranny, Indah Yuri (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Nonsyndromic cleft lip and palate (nsCLP) refers to an abnormal gap in the upper lip and/or palate, without the presence of additional developmental abnormalities. The risk of tooth impaction in nsCLP-patients is greater than in patients without nsCLP. This research aimed to analyze the differences in the tooth impaction characteristics between males and females nsCLP-patients.  Methods: Type of research is cross-sectional study. CLP by observing 64 panoramic radiographs as population, consisting of 28 males and 36 females with the chronological age of over 7 years. The sampling technique used was purposive sampling of tooth impaction and the number of samples are 14. Univariate analysis was performed to examine the data on tooth impaction characteristics. Bivariate analysis was performed to compare the tooth impaction characteristics between males and females. Results: The proportion of tooth impaction in males (28.57%) was greater than in females (16.67%). Tooth impaction generally affects one tooth. Maxillary permanent canines (64.71%) were the most frequently affected teeth. Most of the impacted teeth were located above the cemento-enamel junction, but less than half the length of the adjacent tooth root with unfavorable angulation<650 to the intercondylar line. There were no significant differences in the tooth impaction characteristics, including proportion (p-value=0.5557), number (p-value=0.0644), position (p-value=0.8273), and angulation (p-value=0.8248), between males and females nsCLP-patients. However, there was a significant difference in the type of impacted teeth (p-value=0.0000) between the two genders. Conclusions: There were no differences in the tooth impaction characteristics, including the proportion, number, position, and angulation, except for the type of impacted teeth, between males and females nsCLP-patients. A small proportion of nsCLP-patients was found to have one impacted tooth, with maxillary permanent canines being the most frequently affected teeth. Impacted teeth were commonly located in favorable positions, but with unfavorable angulation.KEYWORDSTooth impaction, nonsyndromic cleft lip and palate, panoramic radiography